1978
DOI: 10.1126/science.694532
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Arcs and Helices

Abstract: Crystals and other regular arrangements of nucleosome cores have been obtained and analyzed in the electron microscope. Two types of regular structures have been studied in detail, the nucleosome arcs and cylinders. The latter are composed of concentric cylindrical layers of intertwined right-handed helices of nucleosome cores. These studies lead to the following conclusions and concepts. The overall structure of the nucleosome core is a short, wedge-shaped cylinder measuring about 110 by 110 by 60 angstroms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…An equivalent interdigitation between the successive helical turns of 30 nm chromatin fibres was proposed previously [2,53,54], and electron microscopy [55,56], X-ray crystallography [1,4,57,58] and modelling studies [5,[25][26][27]59] indicated that nucleosomes have a high tendency to interact through their faces. Furthermore, the intense scattering peak corresponding to a spacing of approximately 6 nm found in a recent synchrotron X-ray scattering study of human mitotic chromosomes [60] also suggests a lateral association between nucleosomes in condensed chromatids.…”
Section: Surface Energy Differences Of Stacked Chromatin Layers Can Ementioning
confidence: 99%
“…An equivalent interdigitation between the successive helical turns of 30 nm chromatin fibres was proposed previously [2,53,54], and electron microscopy [55,56], X-ray crystallography [1,4,57,58] and modelling studies [5,[25][26][27]59] indicated that nucleosomes have a high tendency to interact through their faces. Furthermore, the intense scattering peak corresponding to a spacing of approximately 6 nm found in a recent synchrotron X-ray scattering study of human mitotic chromosomes [60] also suggests a lateral association between nucleosomes in condensed chromatids.…”
Section: Surface Energy Differences Of Stacked Chromatin Layers Can Ementioning
confidence: 99%
“…341 This NCP-NCP stacking governs the formation of NCP columns also in NCP crystals, 342 semicrystalline NCP phases, 343 as well as in NCP arcs and multilayered helices. 344 The side-to-side contacts, with the wrapped DNA duplexes being often in close contact, on the contrary are likely ES in nature, see Fig. 22.…”
Section: B Dense Phases Of Ncpsmentioning
confidence: 99%
“…Predictive power of such theory should however not be over-estimated. The geometrical wedge-shape of NCPs 344,363 and interaction-mediated 364 constraints anticipated for isolated NCPs will interfere with constraints of continuous DNA ''wrapping'' through the fiber structure. Looping and bending of linker DNAs 365 influenced by binding of linker H1/H5 histones is another stabilization mechanisms of a particular forms of ''30 nm'' chromatin fibers.…”
Section: Implications For the Fiber Structurementioning
confidence: 99%
“…These are the only surfaces of the nucleosome that could participate in stereospecific, symmetrical internucleosome contacts (4,30). The arrangement of the nucleosome cores in Fig.…”
mentioning
confidence: 99%
“…Under those conditions, nonhistone proteins and histone H1 are removed from chromatin and the spacer DNA is supercoiled (39). The extra coils in the spacer DNA, which are probably responsible for stacking neighboring nucleosomes onto each other (11), could be the result of overwinding of the duplex DNA by the high salt concentration (30,40,41). Under isotonic conditions, the spacer DNA is not supercoiled (16) and neighboring nucleosomes do not stack onto each other (Fig.…”
mentioning
confidence: 99%